Effect of sovereign rating changes on bond market returns - Cheng, Fan Fah; Lim, Li Hsia; Nasir, Annuar (2014)
Malaysia has just experienced another downgrade of the sovereign rating in July last year, our capital market and currency exchange rate reacted immediately with high loses in Bursa Malaysia couple with sharp depreciation of our currency against major foreign exchanges. Therefore, the main objective of this study is to investigate the effect of sovereign rating changes on bond market returns control for inflation. The importance of sovereign ratings and the growing bond markets are the main motivation for this study. This paper analyse the risk and return relationship of 30 major bond markets which account for 80 percent of world GDP. This paper studies two categories of bond with different maturity period which are1year bond and 10years bond. This study collects Bond yield (YTM) for continuous five years (2007-2011) and the final sample consist of total number of 150 observations for each category of bond. The relationship between bond yields, inflation rates and real yields or inflation adjusted bond yields are examined based on individual observation and portfolio. Findings of portfolios analysis show that all the observations grouped into portfolio, there is negative relationship between sovereign rating and bond yield and positive relationship between inflation rate and bond yield. Finally, hypothesis that test on the relationship between sovereign ratings and real yields is rejected.